MCSE Training Guide: Windows NT Server 4 - Joe Casad, Joe (New Riders Pub, 2011)
Loaded with hundreds of test questions, lists, tables, notes, tips, and tricks, this must-have guide is the most effective, inexpensive, and fastest way to pass the Implementing and Supporting Microsoft Windows NT Server 4.0, or core, exam.